2014
DOI: 10.1002/ps.3781
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide resistance risk assessment based on traits associated with the rate of pathogen evolution

Abstract: Unlike previous methods, trait-based risk assessment can be used to assess resistance risk for fungicides with new modes of action, when there is no prior knowledge of resistance behaviour. Risk predictions using the new method provide a more reliable basis for resistance management decisions. © 2014 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 17 publications
1
52
0
3
Order By: Relevance
“…Evolved resistance to fungicides is a major problem limiting our ability to control agricultural, medical and veterinary pathogens 1, 2. Research over the last 30 years has often defined the mechanism conferring reduced sensitivity to the fungicide.…”
Section: Introductionmentioning
confidence: 99%
“…Evolved resistance to fungicides is a major problem limiting our ability to control agricultural, medical and veterinary pathogens 1, 2. Research over the last 30 years has often defined the mechanism conferring reduced sensitivity to the fungicide.…”
Section: Introductionmentioning
confidence: 99%
“…A strong selective pressure due to repeated use of highly effective fungicides is thought to underlie the cause-effect relationship between fungicide use and resistance evolution. In some cases the strength of selection can lead to rapid fixation of resistance alleles in fungal populations after only a single year of fungicide use (reviewed in Grimmer et al, 2014). In this regard, fungicide resistance evolution is a phenomenon similar to antibiotic resistance evolution (Davies & Davies, 2010), but the literature describing the evolutionary processes that generate, spread and maintain novel resistance alleles in fungal plant pathogens is relatively limited (Chen et al, 2007;Brunner et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A method has been developed (Grimmer et al, 2015) which provides a supplementary predictive method of allocating risk values to pathogens, fungicides and agronomic systems, and then combining those risk values into an overall inherent risk score. This method has been shown (Grimmer et al, 2014) to have higher predictive value than the type of 'risk matrix' approach shown above.…”
Section: Resistance Risk Assessment Based On Traits Associated With Tmentioning
confidence: 99%